A new heuristic approach for assessing losses in power distribution system - Rahmatullah, B.D. (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Electrical and Electronic Engineering, 2018.